The Relationship between Self-efficacy and Students Interpersonal Abilities - Dawir, Randi Saban; Sugiharto, DYP.; Awalya, Awalya (Universitas Negeri Semarang, 2023)
Interpersonal skills are heavily needed by individuals to make social adjustments and resolve interpersonal conflicts. This study attempted to examine the relationship between self-efficacy and students' interpersonal skills. It used a correlational research design with a sample size of 300 students. In collecting the students’ data, a self-efficacy scale and an interpersonal ability scale which have been previously tested for validity and reliability were used. The findings indicated that there was a significant positive relationship between self-efficacy and interpersonal skills. Further implications for guidance and counseling practice are discussed as well.